PENGARUH PENGGUNAAN BAHAN LOKAL PESISIR PANTAI PARANGTRITIS YOGYAKARTA TERHADAP KUAT TEKAN BETON - Retnowati Setioningsih (KURVATEK, 2019)
Research on the use of local coastal materials in Parangtritis Yogyakarta in the manufacture of concrete, is based on its availability in a very large amount of nature. The local materials used are beach sand and "fresh water" obtained from the coast of Parangtritis in Yogyakarta.This study aims to determine the compressive strength of concrete using local materials on the coast of Parangtritis without special treatment.The specimens used were cylindrical with a diameter of 150 mm and height of 300 mm as many as 66 pieces, the study was also controlled using normal concrete using Merapi sand in Yogyakarta. The planned compressive strength is 30 MPa and testing is done at 28 days.From the research, the maximum compressive strength of normal concrete (PM100 PP0 Alab) averaged 31, 066 MPa and specimens using "fresh water" around the coast of Parangtritis (PM100 PP0 Apantai) obtained the average compressive strength of the test object was 30,703 MPa. Keywords: coastal sand, coastal fresh water, concrete compressive strength